Inheriting wisdom: transfer of traditional, scientific, and ecological knowledge in fishing communities in Mexico - Fernández-Rivera Melo, Francisco; Torre, Jorge; Cuevas-Gómez, Gabriela A.; Amador-Castro, Imelda G.; Velázquez-Castillo, Miriam A.; Espinoza-Tenorio, Alejandro (Frontiers in Sustainability, 2024)
The complementary use and transfer of empirical and scientific knowledge are essential for the holistic and sustainable management of fishing resources. To understand how both types of knowledge are transferred in fishing communities in three regions of Mexico, we conducted 120 indepth interviews with young people, adults, and older adults who participated in various activities within fishing value networks. During the interviews, we identified who participated in transferring knowledge within communities, what lessons were passed on, what knowledge has been lost, and what scientific topics are known within the communities. We also investigated the sector's most used means of communication to further explore the transfer of scientific and technical knowledge and the fundamental roles of external actors in transferring knowledge within communities. The information was coded, categorized, and analyzed for each question. The interviewees valued the continuity of inheriting traditional knowledge, which included teaching practical skills, such as fishing techniques and navigation, and transmitting values, traditions, and ways of understanding and relating to the marine environment. The interviewees perceived knowledge transfer as a bidirectional exchange of knowledge, ideas, and practices among generations. Furthermore, they recognized the value of external actors with scientific and technical knowledge in promoting innovation and adapting to new challenges. The combination of knowledge and perspectives enriches fisheries management and marine environmental conservation. Promoting the transfer of traditional and scientific knowledge is fundamental to building a future where fishing and marine life coexist in harmony and prosperity. The responsibility of supporting this integration falls on fishing communities and external actors. Working together in this collaborative learning process is the key to achieving sustainable resource management and ensuring the continuity of this valuable tradition for future generations. In doing so, these communities' cultural and ecological richness can be preserved, ensuring a lasting balance between people and the sea.